Implicit Caputo-Fabrizio fractional differential equations with delay - KRIM, Salim; ABBAS, Saïd; BENCHOHRA, Mouffak; NIETO, Juan J. (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
This article deals with some existence and uniqueness results for several classes of implicit fractional differential equations with delay. Our results are based on some fixed point theorems. To illustrate our results, we present some examples in the last section. Mathematics Subject Classification (2010): 26A33, 34A08, 34K37 Received 01 February 2021; Accepted 22 April 2021. Published Online: 2023-12-11 Published Print: 2023-12-30